A Signaling Theory of Education under the Presence of Career Concerns - Sun Joo Hwang (KDI Journal of Economic Policy, 2016)
A person's life consists of two important stages: the first stage as a student and the second stage as a worker. In an integrated model of education and career concerns, I analyze the welfare effects of education. In Spence's job market signaling model, education as a sorting device improves efficiency by mitigating the lemon market problem. In contrast, in the integrated model, education as a sorting device can be detrimental to social welfare, as it eliminates work incentives generated by career concerns.
Keywords: D86; G38; 330; education; signaling; career concerns